Investigation on the relationship between population synthesis of the honeybee stocks reared in Crete and their resistance to the tracheal mite Acarapis woodi, Rennie - LIAKOS (Β. ΛΙΑΚΟΣ) B. (Journal of the Hellenic Veterinary Medical Society, 2018)
The population synthesis of honey bee breeds reared in Crete by crossbreeding among the native race Apis mellifera adami, Ruttner, the Macedonian bee Apis mellifera macedonica, Ruttner, and the Italian bee Apis mellifera ligustica, Spinal, was determinated. The probable relationship between population synthesis and resistance to tracheal mite Acarapis woodi, Rennie, of these breeds was also investigated. Samples of 50 bees were taken from 45 colonies of an apiary, infested with acarine disease, in which the bees showed a great diversity in their morphological characteristics and were examined as regards: a) the morphological and morphometric characteristics of the sampled bees, and b) the number of infested colonies, the prevalence, the unilateral or bilateral infection and the parasite intensity of thoracic tracheas, from every sample infested by Acarapis woodi. After examination the colonies were classified in four groups, according to morphological and morphometric characteristics that hade the majority of the bees in each sample: Group I, hybrids of Apis mellifera macedonica, group II, hybrids of Apis mellifera ligustica, group III, hybrids of "bright yellow" type of Apis mellifera ligustica, and group IV, diversiform hybrids. From the tracheas examinations it was detected that: the population synthesis affects the resistance of bee colonies. Bee colonies of group I showed the highest resistance. On the contrary, those of group III showed the lowest. Bee colonies of the two other groups showed relatively high resistance but less high than that of A. m. macedonica.